PENTINGNYA iPENDIDIKAN iKARAKTER iSEJAK iDINI iGUNA iMENUMBUHKEMBANGKAN iKESADARAN iBUDAYA iSIKAP iANTI iKORUPTIF i - Sinta iMeidayanti iArifin (Jurnal Ilmu Hukum Sui Generis, 2022)
In ithe icurrent iera iof iglobalization, iwhere ithe iIndonesian ination iis igrowing, iits icharacter ieducation iis igetting iless iand iless. iCharacter iis ia iperson's ipersonality itraits iwhich iinclude iattitudes iand ibehavior, ias iwell ias ithe iway ia iperson iresponds ito iother ipeople. iOne iof ithe ireasons ifor ithe icreation iof icriminal iacts iof icorruption, iespecially iin iIndonesia, iis idue ito ithe ilack iof icharacter ieducation iin ithe iform iof iinstilling ipositive ivalues i​​in iorder ito idevelop icultural iawareness iof ianti-corruption iattitudes ifrom ian iearly iage icarried iout iby ifamilies, iteachers, iand ieven ithe ienvironment iaround ichildren iwhich iis ian iimportant iaspect iin ithe idevelopment iof ichildren's icharacter ifrom ian iearly iage. iIn igeneral, ithe inotion iof icorruption iis iany idishonest iaction ior iact ithat itakes iadvantage iof iposition ior ipower ito igain ibenefits ifor ioneself ior iothers. iFrom ia ireligious iperspective, icorruption iis iseen ias ian iact ithat iis ihighly icommendable iand iis iconsidered idisgraceful. iCases iof icorruption iin iIndonesia ibegan ito iappear iduring ithe iOld iOrder iperiod, iwhere ithe icase iof ireporting ion ithe ialleged icorruption iof iRuslan iAbdulgani iwhich ioccurred ion iAugust i14, i1965 iwas iconsidered ithe ifirst ifailure iin ieradicating icorruption iin iIndonesia. iThere iare ivalues i​​that ineed ito ibe iinstilled ifrom ian iearly iage ias ia iprovision ifor ifuture igenerations iso ithat ithey iare inot iexposed ito icorruption ifrom ian iearly iage. iThe imost ieffective iway ito ideal iwith iacts iof icorruption iis ithrough ithe imedia iof ieducation. iWhere iis ithe ineed ifor ian ianti-corruption ieducation iwhich icontains ithe isocialization iof iforms iof icorruption, ihow ito iprevent iand ireport ias iwell ias ioversight iof icriminal iacts iof icorruption. iEducation ilike ithis imust ibe iinstilled iin ian iintegrated imanner istarting ifrom ielementary ieducation ito itertiary ieducation.